The Service Quality of Community Health Centers During the COVID-19 Pandemic: Do Governance Practices Benefit? - Suryo Pratolo; Arifin Hamsyah Mukti; Hafiez Sofyani (Universitas Muhammadiyah Yogyakarta, Indonesia, 2022)
Research aims: This study aims to examine the role of internal control on the service quality of community health centers in handling the COVID-19 pandemic with transparency and accountability budget management as intervening variables.Design/Methodology/Approach: The population of this study was all community health centers located in the Special Region of Yogyakarta Province. The cluster sampling technique was used in determining the samples. Eighty-two community health centers participated in this study. Data were collected by distributing questionnaires. Partial Least Square (PLS) was employed to test the hypotheses.Research findings: The results revealed that, during the COVID-19 pandemic, internal control implementation was not associated directly with the service quality of the community health center. Instead, the association was mediated by transparency, not accountability. Additionally, transparency independently was associated with service quality.Theoretical contribution/Originality: This study extends the literature by examining the role of good governance mechanisms and principles in the community health center context by positioning transparency and accountability as intervening. In addition, this research was conducted in the context of the COVID-19 pandemic, where the service quality of community health centers has a crucial role in dealing with people exposed to COVID-19.Practitioner/Policy implication: The results of this study can be used as input for the relevant regulator to improve the service quality of community health centers through good governance practices.Research limitation/Implication: This research only involved community health centers in the Special Region of Yogyakarta Province as samples.